Phorbol-12-myristate 13-acetate acting through protein kinase C(ε) induces translocator protein (18-kDa) Tspo gene expression - Batarseh, Amani (2008)
Translocator protein (TSPO) is an 18-kDa cholesterol-binding protein that is expressed at high levels in steroid synthesizing and several cancer cells where it is involved in steroidogenesis and cell proliferation, respectively. The factors regulating Tspo expression are unknown. We analyzed Tspo transcriptional responses to the tumor promoter, phorbol-12-myristate 13-acetate (PMA), in cells with varying TSPO levels. PMA induced Tspo promoter activity and Tspo mRNA levels in TSPO-poor non-steroidogenic cells (NIH-3T3 fibroblasts and COS-7 kidney), but not in TSPO-rich steroidogenic cells (MA-10 Leydig) with high basal Tspo transcriptional activity. The stimulatory effect of PMA was mediated by an 805-515-bp region upstream of the transcription start site. Electrophoretic mobility shift assay (EMSA) revealed that PMA induced binding of c-jun and GA-binding protein transcription factor (GABP-α) to their respective activator protein 1(AP1) and v-ets erythroblastosis virus E26 oncogene homolog (Ets) sites in this region. Protein kinase C (PKC)-specific inhibitors blocked PMA induction of Tspo promoter activity with an inhibition profile suggestive of involvement of PKCε. PKCε expression correlated with TSPO content in the three cell lines. In NIH-3T3 cells, PKCε overexpression induced Tspo promoter activity, mRNA levels and enhanced PMA-induced up regulation of c-jun and TSPO. In MA-10 cells, a PKCε-specific translocation inhibitor peptide reduced basal Tspo promoter activity. PKCε siRNA pool reduced PKCε and TSPO levels in MA-10 cells indicating a role for PKCε in regulating TSPO expression. Taken together, these data suggest that elevated TSPO expression in steroidogenic cells maybe due to high constitutive expression of PKCε that renders them unresponsive to further induction while PMA activation of PKCε drives inducible TSPO expression in non-steroidogenic cells, likely through AP1 and Ets.